2018
DOI: 10.1038/s41598-017-17534-4
|View full text |Cite
|
Sign up to set email alerts
|

A hospital based retrospective study of factors influencing therapeutic leukapheresis in patients presenting with hyperleukocytic leukaemia

Abstract: Therapeutic leukapheresis is a rapid and effective method to reduce early mortality of patients with hyperleukocytic leukaemia (HLL). However, few studies on factors influencing the efficiency have been reported. In this study, 67 cases who underwent leukapheresis were retrospectively analysed and factors related to the collection efficiency of leukapheresis (CEWBC) were also evaluated. Paired t test showed that there was a significant decrease in statistics of white blood cell (WBC) counts after apheresis. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 44 publications
1
13
1
Order By: Relevance
“…Along with the measurable reduction in the leukocyte count in peripheral blood, the patient's spleen shrank to normal size. The mean rate of WBC depletion was 19.1%, ranging from 1% to 34% (Table ), consistent with other similar reports using other apheresis devices . After the 20th leukapheresis session, the WBC count was stabilized at less than 100 × 10 9 cells/L (Fig.…”
Section: Case Presentationsupporting
confidence: 88%
“…Along with the measurable reduction in the leukocyte count in peripheral blood, the patient's spleen shrank to normal size. The mean rate of WBC depletion was 19.1%, ranging from 1% to 34% (Table ), consistent with other similar reports using other apheresis devices . After the 20th leukapheresis session, the WBC count was stabilized at less than 100 × 10 9 cells/L (Fig.…”
Section: Case Presentationsupporting
confidence: 88%
“… 2 A retrospective study by Jin et al attempted to seek factors that influence efficacy of therapeutic leukapheresis in patients with hyperleukocytosis leukemia. 29 In the study, the authors found that lymphocyte count, mean corpuscular hemoglobin (MCH), and hematocrit levels prior to apheresis procedures were independent factors affecting survival. 29 From the study by Jin et al, it can be speculated that there may have been a group of patients that received more benefit from leukapheresis based on lymphocyte count, MCH, and hematocrit levels.…”
Section: Discussionmentioning
confidence: 99%
“…6 Leukapheresis is widely accepted to be very effective in rapid reduction of white blood cell count with up to 70% of leukocytes removed in just a single session. 28,29 However, like all medical treatments and procedures, there are always limitations. The major limitation of leukapheresis is that the procedure does not remove blast cells from bone marrow.…”
Section: Leukapheresis For Aml Patients With Hyperleukocytosismentioning
confidence: 99%
“…Leukocytapheresis along with hydration may help reduce the risk of TLS and complications associated with hyperviscosity, especially in patients with very high TLC [ 3 ]. Leukocytapheresis leads to rapid cytoreduction and does not affect the coagulation parameters [ 4 ].…”
Section: Discussionmentioning
confidence: 99%